RADIOLOGICAL ASSISTANCE IN MANAGING WORKFLOW IN MEDICAL AND SURGICAL INDICATIONS AT SHIFA INTERNATIONAL HOSPITAL IN COVID-19 PANDEMIC - Masood, Laiba; Gul, Salma; Wahla, Madiha saeed; Zafar, Suraya Bano; Akhtar, Samina; Rana, Atif Iqbal (Journal of Ayub Medical College Abbottabad, 2021)
Background: Novel Corona Virus took the world by storm under the name of COVID-19, metamorphosing the whole health care structure and alienating what we the medical community considered normalcy. The sudden unexpected need for social distancing resulted in dire dependency on imaging for expert diagnosis and management. The purpose of the present study is to describe in-depth strategies that were taken by radiology department at our hospital as a part of a coordinated hospital system-wide response in managing workflow of patients presenting to our hospital for various medical and surgical semi-urgent/urgent indications requiring hospital admission. This article may assist and provide guidance for preparation and management for other radiology departments in the early stages or in dire need of providing services in a secure environment, especially in low-income countries such as ours, while maintaining the quality of radiological reports, dealing with increased workloads. It was a descriptive qualitative study, conducted at Shifa international hospital, Radiology Department, from 28 March to 5 June 2020. Methods: After approval from IRB, a descriptive qualitative study was carried out, which included all patients regardless of age or gender who underwent radiological imaging including CT and radiograph chest, at our department from 28 March to 5 June, 2020. Results: Overall, on a yearly basis, the number of CT scans decreased 30% (total), 53.4% (OPD), and 0.61% (IPD), respectively, in 2020 when compared with figures in 2019. However, no. of HRCTs performed were significantly increased compared to 2019, in same months 568 (0.09%), compared to 2020 where a majority of total CTs performed were HRCTs for COVID alone. Conclusion: The radiology department plays a central role in streamlining the patient inflow admitted for surgical or medical indications and thus needs to be prepared for patient surges and increased volumes, with large influxes of patients to the emergency department that will require diagnostic imaging and interventional services.